2012
DOI: 10.7763/ijmlc.2012.v2.189
|View full text |Cite
|
Sign up to set email alerts
|

The Classification of the Applicable Machine Learning Methods in Robot Manipulators

Abstract: Abstract-Supervised machine learning is the search for algorithms that reason from externally supplied instances to produce general hypotheses, which then make predictions about future instances. In other words, the goal of supervised learning is to build a concise model of the distribution of class labels in terms of predictor features. The resulting classifier is then used to assign class labels to the testing instances where the values of the predictor features are known, but the value of the class label is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…As [6] explains, 'the main idea is to maximize the distance between the separating hyper-plane and the closest training example'. After that, new examples are mapped to the same space where it is predicted that they belong to the gap they fall in [11]. According to [7] three main benefits are associated with SVMs.…”
Section: Support Vector Machinesmentioning
confidence: 99%
“…As [6] explains, 'the main idea is to maximize the distance between the separating hyper-plane and the closest training example'. After that, new examples are mapped to the same space where it is predicted that they belong to the gap they fall in [11]. According to [7] three main benefits are associated with SVMs.…”
Section: Support Vector Machinesmentioning
confidence: 99%
“…Nevertheless, there has been compared naïve Bayes classifier with the state-of-the-art methods for induction of decision tree, learning based on instances and rule induction over the standard datasets and it was found that it is superior in some cases to the remaining learning methods. Bayes classifier is having an issue known as attribute-independence which was represented with Averaged One-Dependence Estimators [10]. Rest of the paradigms are based on the perceptron concept.…”
Section: Introductionmentioning
confidence: 99%
“…Optimisation problems often represent very complex tasks and non-heuristic methods are greatly limited in finding proper solutions (Pluhacek et al 2013). A vast number of different algorithms have already been presented in previous literature and they can be classified into a taxonomy based on the type of input available during the training process (Hormozi et al 2012). Supervised learning algorithms are trained on labelled examples and and their main objective consists of generating a function that maps inputs to desired outputs (Kotsiantis et al 2007).…”
Section: Introductionmentioning
confidence: 99%